Spiritual Resistance and Local Adaptation: The Syattariyyah Teachings of Kiai Hasan Maolani in Pre-Exile Kuningan - Novia Poni Agustiyani; Agus Kusman; Akhmad Affandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2026)
This article examines the role of Kiai Hasan Maolani (1782–1874) in introducing and developing the Syattariyyah Sufi order in Kuningan, West Java, during the pre-exile period. Previous studies have tended to emphasize Maolani’s exile and later reputation as a religious figure, while giving limited attention to the formative phase of his religious authority before exile, particularly his activities at the Lengkong pesantren. Addressing this gap, the study asks how Maolani transmitted, localized, and institutionalized Syattariyyah teachings within the local Islamic community. Using historical research methods heuristics, source criticism, interpretation, and historiography. This study reconstructs Maolani’s intellectual, spiritual, and educational influence through available manuscripts, local traditions, and relevant historical sources. The findings show that Maolani’s pesantren functioned not only as a center of Islamic learning but also as a key institution for the dissemination of Syattariyyah doctrine. A distinctive finding is the articulation of a four level dhikr hierarchy, which reflects a structured spiritual pedagogy adapted to local religious needs. This hierarchy demonstrates how Syattariyyah teachings were transmitted through gradual stages of remembrance, discipline, and spiritual refinement. The article argues that Maolani’s pre-exile activities were crucial in shaping the continuity of Syattariyyah in Kuningan and contribute to broader discussions on the localization of Sufi orders, Islamic education, and religious-cultural continuity in Southeast Asia.